Socio-Economic Indicator of Childhood Stunting in Indonesia: A GMM Analysis - Margettya; Suryanto; Gravitiani, Evi (Universitas Negeri Semarang, 2024)
The purpose of this study is to analyze the short-term and long-term effects of socio-economic indicators on the prevalence of stunting in Indonesia in 2018-2022. The estimation used to analyze the spatial dynamic panel data model in this study is the Generalized Method of Moment (GMM). Based on the results of the analysis, the variables that have a significant positive effect on the prevalence of stunting in Indonesia are GRDP per capita and poverty, while the variables of literacy, sanitation and HDI have a negative effect on the prevalence of stunting. Although the effect of GRDP per capita on stunting is weak, if followed by low poverty, increasing literacy spirit, awareness of the importance of sanitation and the continued growth of Indonesia's human development index, it is hoped that every household can provide the nutritional needs of toddlers to quickly reduce the prevalence of stunting in Indonesia.